Mentoring for Breastfeeding Mothers in Stunting Prevention Efforts in Kalasey Dua Village - Pasambo, Yourisna; Karundeng, Yanni; Desyani, Ni Luh Jayanthi; Tuegeh, Johana; Kusmiyati, Kusmiyati (Poltekkes Kemenkes Manado, 2024)
Introduction Stunting occurs in children with chronic malnutrition due to the provision of food that does not meet nutritional needs. Stunting prevention is carried out through specific and sensitive interventions on the target of the first 1,000 days of life, one of which is by providing optimal Exclusive Breastfeeding. The cause of the low coverage of breastfeeding is the lack of understanding and awareness of a mother about the importance of breast milk for child growth. Several previous studies have found that mentoring mothers can increase knowledge and understanding of mothers about the nutrition of pregnant and breastfeeding mothers and the importance of effective Exclusive Breastfeeding. The purpose of the activity is to increase the knowledge and abilities of mothers in providing Exclusive Breastfeeding in Kalasey Dua Village. The community service method is implemented through education on providing Exclusive Breastfeeding using videos and E-Modules as well as face-to-face mentoring and counseling and through WhatsApp groups. The results of the activity showed an increase in the knowledge of pregnant and breastfeeding mothers about providing Exclusive Breastfeeding after being given education and mentoring by implementing videos and e-modules. Conclusion, providing education and mentoring effectively increases the knowledge of pregnant and breastfeeding mothers about the importance of providing Exclusive Breastfeeding.